2013
DOI: 10.1002/grl.50833
|View full text |Cite
|
Sign up to set email alerts
|

Using numerical modeling to explore the origin of intrusion patterns on Fernandina volcano, Galapagos Islands, Ecuador

Abstract: Using parameterized finite element models, we investigate the emplacement of both radial and circumferential intrusions in the configuration observed at Fernandina volcano in the Galapagos Islands. When situated within the edifice at depths consistent with petrological and surface displacement data, inflation of a mildly oblate magma reservoir to the point of rupture can initiate either radial or circumferential intrusions in response to minor, volcanologically plausible variations in reservoir geometry (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…The strong asymmetry of strain and displacement in the dike model reflects the inclination or V-shaped bifurcation of the upper-most section of the dike (Figure 6D). The asymmetry seen in displacement fields produced by model finger and dike intrusions is seen also at Fernandina, and is similarly inferred to be the result of a latestage tilted geometry of the uppermost section of the dikes beneath the eruption sites (Bagnardi et al, 2013;Chestler and Grosfils, 2013).…”
Section: Contributions Of Ct: Intrusion Development and Magma Propagamentioning
confidence: 59%
“…The strong asymmetry of strain and displacement in the dike model reflects the inclination or V-shaped bifurcation of the upper-most section of the dike (Figure 6D). The asymmetry seen in displacement fields produced by model finger and dike intrusions is seen also at Fernandina, and is similarly inferred to be the result of a latestage tilted geometry of the uppermost section of the dikes beneath the eruption sites (Bagnardi et al, 2013;Chestler and Grosfils, 2013).…”
Section: Contributions Of Ct: Intrusion Development and Magma Propagamentioning
confidence: 59%
“…These dikes are forced to twist about an axis parallel to the We also test the case of a gravitationally loaded volcano. We added a body load to a pre-stressed edifice under lithostatic (isotropic) conditions (e.g., Chestler and Grosfils, 2013). This results in pervasive vertical σ1, with only minor deflection (few degrees) in the sub-caldera rock volume.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the best-developed circumferential fissures are found at Fernandina (Gal ‡pagos; Fig1; Chadwick and Howard, 1991), which hosts a ~1 km deep and ~6.5 x 4 km wide caldera resulting from several collapses testified by old benches and a ~350 m drop of the SE caldera floor in the formation of circumferential fissures at Fernandina, considering the effect of: a) caldera faults capturing and channeling magma to the caldera rim (Nordlie, 1973, Browning andGudmundsson, 2015); b) caldera walls unbuttressing re-orienting the minimum compressive stress perpendicular to them (Simkin, 1984;Munro and Rowland 1996); c) stress perturbations due to the pressurization of a magma chamber (Chadwick and Dieterich, 1995;Chestler and Grosfils, 2013) or d) a previous intrusion (Bagnardi et al, 2013). The caldera fault model was excluded based on observing: i) no displacement in layers adjacent to circumferential dikes; ii) circumferential dikes crosscutting caldera faults; and iii) circumferential fissures located well downslope from the caldera rim (Chadwick and Dieterich, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The conditions to develop circumferential dikes remain poorly constrained and, mostly, debated. In fact, at least three differing mechanisms may explain the creation of circumferential dikes: (1) viscous‐dominated shallow intrusion into poorly consolidated rock [ Galland et al , ]; (2) fracturing‐dominated or viscous‐dominated intrusion into cohesive, brittle rock in presence of a radially oriented minimum compressional stress σ 3 possibly due to magma chamber stress [ Chadwick and Dieterich , ; Chestler and Grosfils , ]; and (3) passive occupation of ring faults created during caldera collapse (not discussed here, see instead Anderson [], Gudmundsson [], and Browning and Gudmundsson []). In addition, recent studies also revealed the importance of surface load changes in controlling shallow magma transfer.…”
Section: Introductionmentioning
confidence: 99%